Investigation of light transfer procedure and photobiological hydrogen production of microalgae in photobioreactors at different locations of China. (3rd August 2017) - Zhang, Jun-You; Qi, Hong; He, Zhen-Zong; Yu, Xiao-Ying; Ruan, Li-Ming
Abstract: In this study, the light transfer procedure and photobiological hydrogen production of microalgae in the photobioreactors (PBRs) at different locations of China are investigated thoroughly. Firstly, the solar irradiation projected on the ground of four different regions (Harbin, Beijing, Shanghai and Sanya) at the same moment and that of Harbin at four different moments are calculated by the SMART model. Based on the finite volume method and the photobiological hydrogen production dynamic model, the effects of different irradiance on the photobiological hydrogen production rate in the PBRs are analyzed. In addition, the effect of microalgae cell concentration and the scattering and absorbing of gas bubbles on the hydrogen production have also been studied. All the results elucidate these two factors play a significant role in the light transfer and hydrogen production rate in the PBRs. Meanwhile, the light intensity and microalgae cell density both have the saturation inhibition effect on the hydrogen production process. The distribution of the highly efficient hydrogen production region in the reactor varies with different bubbles concentration. Highlights: The effect of four factors on the light distribution and productivity in the PBRs. The light intensity and microalgae cell density both have the saturation inhibition effect. Good illumination conditions bring high productivity but the low energy utilization efficiency.